Bone histomorphometry and structure in corticosteroid treated chronic active hepatitis. Issue 3 (March 1988) - Stellon, A J; Webb, A; Compston, J E
Abstract : Transiliac biopsies from 34 female patients with corticosteroid treated chronic active hepatitis have been examined to determine the contributions made by decreased bone formation and increased bone resorption to bone loss associated with this condition and to determine the structural basis of the bone loss. Mean wall thickness was significantly reduced when compared with control values (p less than 0.001) as was the bone formation rate at tissue (p less than 0.005) and basic multicellular unit (p less than 0.005) level. The osteoid maturation period and the bone formation period were significantly prolonged (p less than 0.02 and 0.05). The total resorption surfaces were significantly increased (p less than 0.02) but the mean interstitial bone thickness was normal. The mean trabecular plate thickness was significantly reduced (p less than 0.005). These findings indicate that decreased bone formation plays a major role in bone loss associated with corticosteroid treated chronic active hepatitis and that the structural basis of bone loss is trabecular thinning.